Calculation and measurement of mean room surface exitance: The accuracy evaluation. (October 2019) - Dai, Q; Huang, Y; Hao, L; Cai, W
Cuttle proposed mean room surface exitance as a new interior lighting design methodology, which focuses on lit appearance rather than visual performance. A few challenges exist, among which, an easy calculation method and a practical measurement strategy are two important aspects. Cuttle has developed a simplified equation for mean room surface exitance calculation and proposed that mean room surface exitance can be estimated by measuring indirect corneal illuminance from a position that ' brings most of the space into view '; however, no solid proof was provided. In this work, first, we demonstrate that the simplified equation is reasonably accurate by comparing its predictions with the results based on numerical simulation of a wide range of surface reflectance combinations. Two luminaire locations, which are carefully selected to have the same input to the simplified equation but leading to very different surface exitance distributions, are adopted to further verify the simplified equation; second, through a theoretical analysis and numerical simulation, we show that both indirect corneal illuminance and indirect cylindrical illuminance vary significantly with the measurement location and can be very different from mean room surface exitance. Therefore, we conclude that the method of measuring mean room surface exitance suggested in prior publications may not provide accurate results.